Comparison of stimulation sites enhancing dual-task performance using transcranial direct current stimulation in Parkinson’s disease - Seo Jung Yun; Sung Eun Hyun; Woo Hyung Lee; Byung-Mo Oh; Han Gil Seo (npj Parkinson's Disease)
Abstract This pilot randomized crossover study aimed to compare the effects of stimulating various transcranial direct current stimulation (tDCS) target sites to improve dual-task performance in patients with Parkinson’s disease (PD). Nineteen patients with idiopathic PD completed four sessions of 2 mA anodal tDCS for 20 min at randomly assigned sites: the primary motor cortex (M1), left dorsolateral prefrontal cortex (DLPFC), ventromedial prefrontal cortex, and sham stimulation. Anodal M1 tDCS induced statistically significant improvements in single-task and cognitive dual-task timed up and go test. Additionally, enhancements were noted in the color-word Stroop test and trail-making test-Trail B following left DLPFC stimulation. However, none of the stimulation sites showed any significant changes in the dual-task effect. Overall, these results suggest that although tDCS targeting the M1 and DLPFC may immediately enhance motor and cognitive performances, respectively, neither has a significant effect on dual-task interference.